Repatriating Polanyi: Market Society in the Visegrad States - Hann, Chris (Central European University Press, 2019)
Karl Polanyi’s “substantivist” critique of market society has renewed topicality in the era of neoliberal globalization. Polanyi (1886–1964) is popular among critical theorists and radical political economists, but also with ecological activists, anti-globalization campaigners and all who sense that ongoing financial turmoil is symptomatic of a deeper crisis threatening the compatibility of capitalism and democracy. The author reclaims the polymath Karl Polanyi for contemporary anthropology, especially economic anthropology. The book furthermore takes his ideas back to Central Europe, where he grew up. The Polanyian approach is applied to the communist economy, with particular reference to the “market socialist” economy which evolved under János Kádár in Hungary. The same lens is used to investigate the consequences of the demise of communist power since 1990, primarily on the basis of ethnographic investigations in Hungary and South-East Poland. Stretching the discussion on Polanyi’s great transformation – for which there is considerable international interest – in the context of neoliberalization onto the concept of Eurasia, and then bringing this into conversation with the rise of neo-nationalism in Hungary and Poland and beyond as the form that the great transformation is currently taking in the region, relates Hann’s work powerfully to the current political turbulence.
Keywords: Hungary; Poland; communist economy; economic history; market socialist economy; neo-nationalism; political economy

Polanyi in times of populism: Vision and contradiction in the history of economic ideas - Holmes, Christopher (Routledge, 2018)
The rise of populism across Europe and the US – first in the wake of the 2008 global financial crisis and then in the shape of Donald Trump’s presidential campaign and the Brexit vote in 2016 – are indicative of a seismic shift in the terrain of economic ideas in public discourse. Settled liberal norms concerning ever-increasing international market expansion, and the political integration required to sustain it, have been decisively upset by political forces that, whilst once on the fringes, now dominate economic debate. How might we make sense of this ideological breakdown and what might we hope for next? This book turns to the work of Karl Polanyi for answers, developing the expansive, historicised approach to political economy that Polanyi pioneered. Holmes provides a wide-ranging history of economic ideas read in terms of a series of hopeful theoretical visions of order, in which political, social and ecological contradictions could be transcended in one way or another. Through this, the book demonstrates that the failing utopian visions of pre-2008 economic orthodoxy, which have formed the backdrop to the rise of populism today, are only the latest in a series that stretches across economic thought in Western modernity as a whole. This book will interest students and scholars of IPE, political science, sociology, anthropology, law and history.
Keywords: political science / general; populism

Costly Fix: Power, Politics, and Nature in the Tar Sands - Urquhart, Ian Thomas (University of Toronto Press, 2018)
Costly Fix examines the post-1995 Alberta tar sands boom, detailing how the state inflated the profitability of the tar sands and turned a blind eye to environmental issues. It considers the position of First Nations, the character and strength of environmental critiques, and the difficulties that environmental groups and First Nations have had in establishing a countermovement to market fundamentalism. The final chapter discusses how Alberta's new NDP government, in its first couple of years, has addressed the legacies they have inherited from the previous Progressive Conservative government on climate change, royalties, and the blight of tailings ponds in the boreal forest. Throughout the book, Urquhart demonstrates that too many actors have done too little to prevent Alberta's boreal forest from becoming a landscape sacrificed for unsustainable economic growth.
Keywords: Alberta; Canada; First Nations; double movement; environmentalism; tar sands

Capitalism: A Conversation in Critical Theory - Fraser, Nancy; Jaeggi, Rahel (John Wiley & Sons, 2018)
In this important new book, Nancy Fraser and Rahel Jaeggi take a fresh look at the big questions surrounding the peculiar social form known as “capitalism,” upending many of our commonly held assumptions about what capitalism is and how to subject it to critique. They show how, throughout its history, various regimes of capitalism have relied on a series of institutional separations between economy and polity, production and social reproduction, and human and non-human nature, periodically readjusting the boundaries between these domains in response to crises and upheavals. They consider how these “boundary struggles” offer a key to understanding capitalism’s contradictions and the multiple forms of conflict to which it gives rise. What emerges is a renewed crisis critique of capitalism which puts our present conjuncture into broader perspective, along with sharp diagnoses of the recent resurgence of right-wing populism and what would be required of a viable Left alternative. This major new book by two leading critical theorists will be of great interest to anyone concerned with the nature and future of capitalism and with the key questions of progressive politics today.
Keywords: boundary struggle; capitalism; political philosophy; triple movement

What American Government Does - Luger, Stan; Waddell, Brian (JHU Press, 2017)
It has become all too easy to disparage the role of the US government today. Many Americans are influenced by a simplistic anti-government ideology that is itself driven by a desire to roll back the more democratically responsive aspects of public policy. But government has improved the lives of Americans in numerous ways, from providing income, food, education, housing, and healthcare support, to ensuring cleaner air, water, and food, to providing a vast infrastructure upon which economic growth depends. In What American Government Does, Stan Luger and Brian Waddell offer a practical understanding of the scope and function of American governance. They present a historical overview of the development of US governance that is rooted in the theoretical work of Charles Tilly, Karl Polanyi, and Michael Mann. Touching on everything from taxes, welfare, and national and domestic security to the government’s regulatory, developmental, and global responsibilities, each chapter covers a main function of American government and explains how it emerged and then evolved over time. Luger and Waddell are careful to both identify the controversies related to what government does and those areas of government that should elicit concern and vigilance. Analyzing the functions of the US government in terms of both a tug-of-war and a collaboration between state and societal forces, they provide a reading of American political development that dispels the myth of a weak, minimal, non-interventionist state. What American Government Does represents a major contribution to the scholarly debate on the nature of the American state and the exercise of power in America. -- Sidney Plotkin, Vassar College, coauthor of Private Interests, Public Spending: Balanced-Budget Conservatism and the Fiscal Crisis
Keywords: American government; history - Americas (North, Central, South, West Indies); political science - history and theory

Karl Polanyi in Dialogue: A Socialist Thinker for our Times - Brie, Michael (Black Rose Books, 2017)
Featuring essays from Michael Brie (Rose Luxemburg Foundation, Berlin), Nancy Fraser (New School for Social Research, New York) and Kari Polanyi-Levitt (McGill University, Montreal). The contemporary Left fights its political battles on various fronts: protesting the crippling structural inequalities that sustain neoliberal economic policy; developing sustainable, community-based alternatives to the consumerism and short-termism that exacerbate the environmental crisis; and advocating for the cultural recognition, emancipation and celebration of the diversity and pluralism of human identity. But despite this versatility the Left appears to be in worldwide retreat whilst an aggressive new ‘Alt-Right’ is taking to the internet and the streets, regurgitating a regressive and patriarchal vision of society that has already won startling political victories in the US and Europe. Amidst the vertiginous tension of such a crisis, Michael Brie argues for an urgent theoretical and practical reorganisation of the Left. Developing the work of philosopher and social theorist Karl Polanyi, Brie advocates an alliance of socialist liberals and libertarian ‘commonists’ that unites contemporary campaigns for recognition, difference and human dignity with more traditional struggles for social welfare and economic democracy. Starting with Nancy Fraser’s critical reappraisal of Polanyi in her article “A Triple Movement? Parsing the Politics of Crisis after Polanyi” (included), Brie powerfully reinterprets Polanyi’s thought for present times, developing concrete proposals for a Polanyian political response to neoliberalism, an ascendent authoritarian right and the ongoing threat of global ecological disaster. Also included are two articles by Polanyi translated into English for the first time and Kari Polanyi-Levitt’s lecture at the Rosa Luxemburg Foundation “From the Great Transformation to the Great Financialisation”.
Keywords: biography; ecology; economics; feminism; history; labor; labour; politics; racism; sociology

The moral economists: R.H. Tawney, Karl Polanyi, E. P. Thompson, and the critique of capitalism - Rogan, Tim (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism--R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."
Keywords: HENRY, Richard; PALMER, Edward; TAWNEY, R.H.; THOMPSON, E.P.; capitalism; moral and ethical aspects; moral economy; socialism

How Will Capitalism End?: Essays on a Failing System - Streeck, Wolfgang (Verso Books, 2016)
The provocative political thinker asks if it will be with a bang or a whimperAfter years of ill health, capitalism is now in a critical condition. Growth has given way to stagnation; inequality is leading to instability; and confidence in the money economy has all but evaporated.In How Will Capitalism End?, the acclaimed analyst of contemporary politics and economics Wolfgang Streeck argues that the world is about to change. The marriage between democracy and capitalism, ill-suited partners brought together in the shadow of World War Two, is coming to an end. The regulatory institutions that once restrained the financial sector’s excesses have collapsed and, after the final victory of capitalism at the end of the Cold War, there is no political agency capable of rolling back the liberalization of the markets.Ours has become a world defined by declining growth, oligarchic rule, a shrinking public sphere, institutional corruption and international anarchy, and no cure to these ills is at hand.
Keywords: political science / globalization; political science / political economy; political science / political ideologies / democracy

Karl Polanyi: The Hungarian Writings - Dale, Gareth (Oxford University Press, 2016)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology, and social policy. The volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. The workshop was opened by Kari Polanyi-Levitt, who also has written the Introductory Foreword to this book. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations, and European labour markets.
Keywords: history - modern; political history; political philosophy; political theory

The Commonalities of Global Crises: Markets, Communities and Nostalgia - Karner, Christian; Weicht, Bernhard (Springer, 2016)
Bringing together contributions from an international group of social scientists, this collection examines diverse crises, both historical and contemporary, which implicate market forces, widening inequalities, social exclusion, forms of resistance, and ideological polarisation. The Commonalities of Global Crises offers carefully researched case studies which stretch across large geographical distances- from Egypt to the US and from northern, central, eastern and southern Europe to South America- and covers timely issues including human rights, slavery, care, migration, racism, and the far right. The volume demonstrates that such different settings and diverse concerns are characterized by a common tension in which the crises that unfold around pressures of widening marketization and commodification are met by the (re)building or re-assertion of various communities, and competing politics of solidarity and nostalgia.
Keywords: business & economics / general; commodification; disembedding; double movement; economic theory; political science / general; social science / general

Bourgeois Equality: How Ideas, Not Capital or Institutions, Enriched the World - McCloskey, Deirdre N. (University of Chicago Press, 2016)
There’s little doubt that most humans today are better off than their forebears. Stunningly so, the economist and historian Deirdre McCloskey argues in the concluding volume of her trilogy celebrating the oft-derided virtues of the bourgeoisie. The poorest of humanity, McCloskey shows, will soon be joining the comparative riches of Japan and Sweden and Botswana.   Why? Most economists—from Adam Smith and Karl Marx to Thomas Piketty—say the Great Enrichment since 1800 came from accumulated capital. McCloskey disagrees, fiercely. “Our riches,” she argues, “were made not by piling brick on brick, bank balance on bank balance, but by piling idea on idea.” Capital was necessary, but so was the presence of oxygen. It was ideas, not matter, that drove “trade-tested betterment.”  Nor were institutions the drivers. The World Bank orthodoxy of “add institutions and stir” doesn’t work, and didn’t. McCloskey builds a powerful case for the initiating role of ideas—ideas for electric motors and free elections, of course, but more deeply the bizarre and liberal ideas of equal liberty and dignity for ordinary folk. Liberalism arose from theological and political revolutions in northwest Europe, yielding a unique respect for betterment and its practitioners, and upending ancient hierarchies. Commoners were encouraged to have a go, and the bourgeoisie took up the Bourgeois Deal, and we were all enriched.   Few economists or historians write like McCloskey—her ability to invest the facts of economic history with the urgency of a novel, or of a leading case at law, is unmatched. She summarizes modern economics and modern economic history with verve and lucidity, yet sees through to the really big scientific conclusion. Not matter, but ideas. Big books don’t come any more ambitious, or captivating, than Bourgeois Equality. KM - Part IV heavily engages with Polanyi's ideas, including embeddedness
Keywords: Europe; business & economics; economic history; embeddedness; history; political science; political theory; social science

The Great Acceleration: An Environmental History of the Anthropocene since 1945 - McNeill, J. R. (Harvard University Press, 2016)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age—the Anthropocene. Humans have altered the planet’s biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.
Keywords: anthropocene; history / modern / 20th Century; history / world; nature / environmental conservation & protection; political science / public policy / environmental policy

Reconstructing Karl Polanyi - Dale, Gareth (Pluto Press, 2016)
Karl Polanyi was one of the most influential political economists of the twentieth-century and is widely regarded as the most gifted of social democrat theorists. In Reconstructing Karl Polanyi, Gareth Dale draws upon primary sources archived in the countries that Polanyi called home—Hungary, Austria, Britain, the United States, and Canada—to provide a sweeping survey of his contribution to the social sciences. Polanyi’s intellectual and political outlook can best be summarized through paradoxical formulations such as ‘romantic modernist’, ‘liberal socialist’, and ‘cosmopolitan patriot.’ In exploring these paradoxes, Dale excavates and reconstructs Polanyi’s views on a range of topics that have been neglected in the critical literature, including Keynesian economic policy, the evolution and dynamics of Stalin’s Russia, regional integration, and McCarthyism. He reinterprets Polanyi’s philosophy of history, his theory of democracy, and his economic historiography of Ancient Greece and Mesopotamia, and guides readers through Polyani's critical dialogue with Marxism. While the central threads and motifs of this study are intellectual-historiographical in nature, Dale also critically analyzes the views of Polanyi and his followers on issues of pressing present-day relevance, notably the clash between democracy and capitalism, and the nature and trajectory of European unification.
Keywords: political theory; social theory

The Great Mindshift: Linking Forerunners of a New Sustainability Paradigm - Gopel, Maja (Brookings Inst Press, 2015)
Making sustainability a policy goal is one of the greatest challenges of the 21st century. Calls for a paradigm shift are becoming increasingly frequent and urgent. In fact, change toward a sustainable form of society seems to be more within reach than ever before. The mindset of people has changed in the course of economic and environmental crises. This publication presents the current scientific and practical approaches that shape and empower the process of change toward true sustainability. It also raises the question as to the new possibilities that may arise from linking these approaches.
Keywords: environmental policy; environmental science; global warming & climate change; public policy; science

Greening of Capitalism: How Asia Is Driving the Next Great Transformation - Mathews, John (Stanford University Press, 2014)
As China, India, and other industrializing giants grow, they are confronted with an inconvenient truth: They cannot rely on the conventions of capitalism as we know them today. Western industrialism has achieved miracles, promoting unprecedented levels of prosperity and raising hundreds of millions out of poverty. Yet, if allowed to proceed unencumbered, this paradigm will do irreversible harm to the planet. By necessity, a new approach to environmentally conscious development is already emerging in the East, with China leading the way. Positioning its argument against zero-growth advocates and free-market environmentalists, Greening of Capitalism charts this transformation and sketches out a framework for more sustainable capitalism. State-mandated changes in energy use (as opposed to carbon taxes), a circular flow of resources (as opposed to emissions standards), and the introduction of new financial instruments that support green growth are cornerstones of China's framework. John A. Mathews argues that these tenets will be emulated around the worldfirst in India and Brazil. In light of this emerging shift, Mathews considers core debates over national security, international relations, and economic policy, ultimately addressing the question of whether these measures will be far-reaching or timely enough to prevent further damage.
Keywords: business & economics; economic policy; energy; government & business; industries; public policy; sustainable capitalism

Making Capitalism Fit For Society - Crouch, Colin (John Wiley & Sons, 2014)
Capitalism is the only complex system known to us that can provide an efficient and innovative economy, but the financial crisis has brought out the pernicious side of capitalism and shown that it remains dependent on the state to rescue it from its own deficiencies. Can capitalism be reshaped so that it is fit for society, or must we acquiesce to the neoliberal view that society will be at its best when markets are given free rein in all areas of life? The aim of this book is to show that the acceptance of capitalism and the market does not require us to accept the full neoliberal agenda of unrestrained markets, insecurity in our working lives, and neglect of the environment and of public services. In particular, it should not mean supporting the growing dominance of public life by corporate wealth. The world’s most successful mature economies are those that fully embrace both the discipline of the market and the need for protection against its negative outcomes. Indeed, a continuing, unresolved clash between these two forces is itself a major source of vitality and innovation for economy and society. But maintenance of that tension depends on the enduring strength of trade unions and other critical groups in civil society - a strength that is threatened by neoliberalism’s increasingly intolerant onward march. Outlining the principles for a renewed and more assertive social democracy, this timely and important book shows that real possibilities exist to create a better world than that which is being offered by the wealthy elites who dominate our public and private lives.
Keywords: business & economics; capitalism; economic theory

The Passage West: Philosophy After the Age of the Nation State - Marramao, Giacomo (Verso Books, 2014)
In this ambitious work, Giacomo Marramao proposes a radical reconceptualization of the world system in our era of declining state sovereignty. He argues that globalization cannot be reduced to mere economics or summarized by phrases such as ‘the end of history’ or the ‘westernization of the world’. Instead, we find ourselves embarking on a passage to a new, post-nation state age destined to transform all civilizations – and to disrupt Western geopolitical dominance. To confront the challenges of this interregnum one must think in terms of a new and radical universalism, a universalism of difference able to revitalize politics and to demythologize identity.Building on the great interwar discussion between Spengler, Junger, Schmitt and Heidegger, Marramao’s new work engages with Habermas, Derrida and post-colonialism. Arguing against the classic Western pretension to universal norms of democracy and reason, he develops instead the idea of a ‘universal politics of difference’. KM - contains chapter: Gift, exchange, obligation: Karl Polanyi and social philosophy
Keywords: exchange; international relations; religious philosophy; social philosophy

The Rise and Fall of Ireland's Celtic Tiger: Liberalism, Boom and Bust - Ó Riain, Seán (Cambridge University Press, 2014)
In 2008 Ireland experienced one of the most dramatic economic crises of any economy in the world. It remains at the heart of the international crisis, sitting uneasily between the US and European economies. Not long ago, however, Ireland was celebrated as an example of successful market-led globalisation and economic growth. How can we explain the Irish crisis? What does it tell us about the causes of the international crisis? How should we rethink our understanding of contemporary economies and the workings of economic liberalism based on the Irish experience? This book combines economic sociology and comparative political economy to analyse the causes, dynamics and implications of Ireland's economic 'boom to bust'. It examines the interplay between the financial system, European integration and Irish national politics to show how financial speculation overwhelmed the economic and social development of the 1990s 'Celtic Tiger'.
Keywords: business & economics; economic conditions; economic development; economic history; economic policy; liberalism; political science; public policy

The Global Development Crisis - Selwyn, Benjamin (John Wiley & Sons, 2014)
The central paradox of the contemporary world is the simultaneous presence of wealth on an unprecedented scale, and mass poverty. Liberal theory explains the relationship between capitalism and poverty as one based around the dichotomy of inclusion (into capitalism) vs exclusion (from capitalism). Within this discourse, the global capitalist system is portrayed as a sphere of economic dynamism and as a source of developmental opportunities for less developed countries and their populations. Development policy should, therefore, seek to integrate the poor into the global capitalist system. The Global Development Crisis challenges this way of thinking. Through an interrogation of some of the most important political economists of the last two centuries Friedrich List, Karl Marx, Leon Trotsky, Joseph Schumpeter, Alexander Gerschenkron, Karl Polanyi and Amarta Sen, Selwyn argues that class relations are the central cause of poverty and inequality, within and between countries. In contrast to much development thinking, which portrays ‘the poor’ as reliant upon benign assistance, this book advocates the concept of labour-centred development. Here ‘the poor’ are the global labouring classes, and their own collective actions and struggles constitute the basis of an alternative form of non-elitist, bottom-up human development.
Keywords: business & economics / development; economic development; embedded markets; political science / public policy / general; socialism

L'économie solidaire en Bolivie. Entre marché et démocratie - Hillenkamp, Isabelle (KARTHALA Editions, 2013)
Depuis les années 1980, de plus en plus de pays ont opté pour une économie de marché et un régime politique de type démocratique et ce, indépendamment de leur « niveau de développement ». Pourtant, marché et démocratie ne sont pas directement compatibles. Si tous deux reposent sur les principes de liberté et d’égalité, le premier mise sur le pouvoir émancipateur du marché libre, alors que la seconde suppose une certaine égalité des conditions de vie. Une lecture croisée de cas européens et latino-américains illustre cette problématique commune, en même temps que la diversité des systèmes de médiations solidaires entre marché et démocratie. Les solidarités, qu’elles soient enracinées dans des structures familiales ou communautaires, instituées dans des systèmes de protection sociale ou organisées dans des groupes de producteurs ou de consommateurs de l’économie solidaire, créent en effet des interdépendances qui amortissent les tensions entre marché et démocratie. En développant cette analyse socioéconomique, Isabelle Hillenkamp propose une approche novatrice des questions de développement. Par des données récoltées auprès d’organisations d’économie solidaire et de nombreux autres acteurs en Bolivie, elle apporte des réponses ancrées dans la complexité d’un terrain de recherche. Isabelle Hillenkamp est titulaire d’un doctorat en études du développement de l’Institut de hautes études internationales et du développement, à Genève. A partir d’enquêtes en Amérique latine, ses travaux portent sur l’économie populaire et solidaire, qu’elle aborde dans une perspective socioéconomique, attentive aux liens entre pratiques économiques et rapports sociaux. Elle est chargée de recherche à l’Institut de recherche pour le développement, en France. Table des matières Introduction, L’économie solidaire en Bolivie, Entre marché et démocratie, Du pluralisme économique à la démocratisation I. Solidarité, marché et démocratie : une problématique européenne et latino-américaine II. Les organisations boliviennes d’économie solidaire : réciprocité et redistribution III. Les organisations boliviennes d’économie solidaire face aux marchés IV. Réciprocité, marché et démocratie : des tensions fondamentales V. La démocratisation de l’économie Ils en ont parlé Présentation du livre dans L'AGEFI, quotidien de l'Agence économique et financière à Genève Critique du livre sur le site Alterinfos, América Latina ENG translation: Since the 1980s, more and more countries have opted for a market economy and a democratic-type political regime, irrespective of their "level of development". Yet market and democracy are not directly compatible. If both are based on the principles of liberty and equality, the first is the emancipatory power of the free market, while the latter assumes a certain equality of living conditions. A cross-reading of European and Latin American cases illustrates this common problem, together with the diversity of solidarity-based mediation systems between market and democracy. Solidarity, whether rooted in family or community structures, instituted in social protection systems or organized in groups of producers or consumers of the solidarity economy, creates interdependencies that dampen tensions between the market and democracy. In developing this socioeconomic analysis, Isabelle Hillenkamp proposes an innovative approach to development issues. Through data collected from organizations of solidarity economy and many other actors in Bolivia, it brings answers anchored in the complexity of a field of research. Isabelle Hillenkamp holds a Ph.D. in Development Studies from the Graduate Institute of International and Development Studies in Geneva. Based on surveys in Latin America, her work focuses on the popular and solidarity economy, which she addresses in a socio-economic perspective, attentive to the links between economic practices and social relations. She is a researcher at the Research Institute for Development in France. Table of Contents Introduction, Solidarity Economy in Bolivia, Between Market and Democracy, From Economic Pluralism to Democratization I. Solidarity, Market and Democracy: A European and Latin American Issue II. Bolivian organizations of solidarity economy: reciprocity and redistribution III. Bolivian organizations of solidarity-based economy versus markets IV. Reciprocity, market and democracy: fundamental tensions V. The democratization of the economy They talked about it Presentation of the book in the AGEFI, the daily newspaper of the Economic and Financial Agency in Geneva Book review on the website Alterinfos, América Latina
Keywords: Bolivia; solidarity economy

From the Great Transformation to the Great Financialization: On Karl Polanyi and Other Essays - Polanyi Levitt, Kari (Zed Books, 2013)
Four years into the unfolding of the most serious crisis since the 1930s, Karl Polanyi's prediction of the fateful consequences of unleashing the destructive power of unregulated market capitalism on peoples, nations, and the natural environment have assumed new urgency and relevance. Polanyi's insistence that 'the self-regulating market' must be made subordinate to democracy otherwise society itself may be put at risk is as true today as it was when Polanyi wrote. Written from the unique perspective of his daughter, From the Great Transformation to the Great Financialization is an essential contribution to our understanding of the evolution and contemporary significance of Karl Polanyi's work, and should be read against the background of the accelerating accumulation of global finance that created a series of financial crises in Latin America, Russia, Asia, and, eventually, the heartlands of capitalism itself.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Latin America; business & economics; economic conditions; economic development; economic history; global financial crisis; political economy; political science

Fortunes of Feminism: From State-Managed Capitalism to Neoliberal Crisis - Fraser, Nancy (Verso Books, 2013)
Charts the history of women’s liberation and calls for a revitalized feminism.Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.During the ferment of the New Left, “Second Wave” feminism emerged as a struggle for women’s liberation and took its place alongside other radical movements that were questioning core features of capitalist society. But feminism’s subsequent immersion in identity politics coincided with a decline in its utopian energies and the rise of neoliberalism. Now, foreseeing a revival in the movement, Fraser argues for a reinvigorated feminist radicalism able to address the global economic crisis. Feminism can be a force working in concert with other egalitarian movements in the struggle to bring the economy under democratic control, while building on the visionary potential of the earlier waves of women’s liberation. This powerful new account is set to become a landmark of feminist thought.
Keywords: critical theory; feminism; feminist theory; triple movement

Europe and Problems of Marketization: from Polanyi to Scharpf - Crouch, Colin (Firenze University Press, 2013)
The author uses the theory of the 'Great Transformation' of the industrialisation of England developed by Karl Polanyi to describe the current situation in Europe. There is a strong marketisation of the economy and also of social life, but what is missing is the social policy that needs to accompany this process, if there are not to be major problems. From this perspective marketization and social policy do not exist in a zero-sum game, but are mutually dependent. The emphasis on negative rather than positive integration (to use the terms conceived by Fritz Scharpf) in the development of Europe makes this interdependence more difficult to achieve. The division of competences between the European level (market policies) and the nation states (social policies) makes this situation even worse. The only way forward is a strengthening of the European social dimension.
Keywords: Europe; business & economics; commodification; economic theory; social policy

Socioéconomie et démocratie, l'actualité de Karl Polanyi - Hillenkamp, Isabelle; Laville, Jean-Louis (Toulouse : Érès éd, 2013)
La crise actuelle révèle des tensions fondamentales entre capitalisme et démocratie. L'orthodoxie occidentale, centrée sur les programmes d'ajustement, s'avère incapable d'affronter ce défi à la frontière de l'économie, du social et du politique. Il est temps de se tourner vers d'autres approches. S'appuyant sur l'oeuvre singulière de Karl Polanyi (1886- 1964) qui a décelé la dérive totalitaire de la société de marché, cet ouvrage soumet de nouvelles clés pour penser certains des problèmes les plus ardus de notre temps. Les auteurs, internationalement reconnus, venant d'Amérique et d'Europe, du Sud et du Nord, sont publiés pour la première fois ensemble en langue française. Ils proposent une vision croisée des rapports entre démocratie et économie, à partir de différentes disciplines et de divers terrains d'étude. Cette réflexion collective débouche sur la construction d'un cadre théorique permettant de comprendre la teneur des mutations économiques et politiques contemporaines. Mais elle ne s'arrête pas aux constats critiques. Face à la menace d'une régression autoritaire, elle s'intéresse aux pratiques qui concrétisent des issues solidaires et démocratiques à la crise. ENG: The aim of this book is to mobilize the contribution of Polanyi to think the socio-economy in a perspective of deepening democracy. The book updates the critical analysis of the new globalized capitalism but also identifies socio-economic experiences that can contribute to building more democratic societies in the 21st century.
Keywords: démocratie; développement économique - aspect social; economics - sociological aspects; triple movement; économie de marché; économie politique - aspect sociologique; économie sociale; économie sociale et solidaire

The Embedded Firm: Corporate Governance, Labor, and Finance Capitalism - Williams, Cynthia A.; Zumbansen, Peer (Cambridge University Press, 2011)
The globalization of capital markets since the 1980s has been accompanied by a vigorous debate over the convergence of corporate governance standards around the world towards the shareholder model. But even before the financial and economic crisis of 2008/2009, the dominance of the shareholder model was challenged with regard to persisting divergences and national differences in corporate law, labor law and industrial relations. This collection explores this debate at an important crossroads, echoing Karl Polanyi's famous observation in 1944 of the disembeddedness of the market from society. Drawing on pertinent insights from scholars, practitioners and regulators in corporate and labor law, securities regulation as well as economic sociology and management theory, the contributions shed important light on the empirical effects on the economy of the shift to shareholder primacy, in light of a comprehensive reconsideration of the global context, policy goals and regulatory forms which characterize market governance today.
Keywords: business & economics / management; corporate governance; disembeddedness; international law; political science / public policy / economic policy

Karl Polanyi, Globalisation and the Potential of Law in Transnational Markets - Joerges, Christian; Falke, Josef (Hart, 2011)
The patterns and impact of globalization have become a common concern of all international jurists, sociologists, political scientists, and philosophers. Many have observed the erosion of the powers of nation states and the emergence of new transnational governance regimes, and seek to understand their internal dynamics, re-regulatory potential, and normative quality. Karl Polanyi's seminal book - The Great Transformation - is attracting new attention to such endeavors, mirroring a growing sensitivity to the social and economic risks of dis-embedding politics. Their re-construction by Polanyi - including his warning against a commodification of labor, land, and money - provide the trans-disciplinary reference point for the contributions to this book. Political economy, political theory, sociology, and political science inform this discussion of Polanyi's insights in the age of globalization. Further theoretical essays and case studies look at his 'false commodities': money, labor (and services), and land (and the environment). Jurists have hardly ever discussed Polanyi, and the law has not been taken very seriously among 'Polanyians.' It is nevertheless clear that economic stability and social protection are simply inconceivable without the visible hand of law. The legal discussion in this book's concluding chapters do not, and cannot, depart directly from such premises. The framework of their analyses is, instead, informed by current debates on the emergence of para-legal regimes, the fragmentation of international law, and the prospects of constitutional perspectives within which the rule of law and the notion of law-mediated legitimate governance are established. Polanyi's notion of the co-originality of dis-embedding moves and re-imbedding countermoves can, however, be usefully employed in the re-construction of the sociological background of the moves and tensions which jurists discern.
Keywords: conflict of laws; jurisprudence; law - commercial; political science - history and theory

Work After Globalization: Building Occupational Citizenship - Standing, Guy (Edward Elgar Publishing, 2010)
Per Google Books: This is a scholarly and erudite work. . . There is a wealth of detail, all illustrated with plenty of fascinating examples. . . It is impossible to give the full flavour of this thoughtful and stimulating book in even a long review, but it deserves to be
Keywords: business & economics - labor; business & economics - labour; embeddedness; industrial citizenship; political science / labor & industrial relations; political science / labour & industrial relations; social science / sociology / general

Karl Polanyi: the limits of the market - Dale, Gareth (Key contemporary thinkers series, 2010)
Karl Polanyi: The Limits of the Market is the first comprehensive introduction to Polanyi's ideas and legacy. It assesses not only the texts for which he is famous – prepared during his spells in American academia – but also his journalistic articles written in his first exile in Vienna, and lectures and pamphlets from his second exile, in Britain. It provides a detailed critical analysis of The Great Transformation, but also surveys Polanyi’s seminal writings in economic anthropology, the economic history of ancientand archaic societies, and political and economic theory. Its primary source base includes interviews with Polanyi's daughter, Kari Polanyi-Levitt, as well as the entire compass of his own published and unpublished writings in English and German. This engaging and accessible introduction to Polanyi's thinkingwill appeal to students and scholars across the social sciences,providing a refreshing perspective on the roots of our currenteconomic crisis.
Keywords: economics; philosophy

Transformation als historischer Prozess: Karl Polanyi - Rebmann, Mara; Marmuth, Juliane (GRIN Verlag, 2010)
KM translate: Polanyi starts from the thesis that only the emergence of a liberal market economy with its "free play of the forces" led to that characteristic "separation" and self-sufficiency of the economy against society, which historically represents a novelty and bourgeois society of all others Distinguishes social information. With this thesis, the complex transformation of societies through the interaction with the economic order on the basis of Polanyi's work The Great Transformation will be descriptively explained and discussed. Here are his theses taken up and explained from his point of view.
Keywords: Great Transformation, The (Book)

Challenging Neoliberalism in Latin America - Silva, Eduardo (Cambridge University Press, 2009)
At the turn of the twentieth century, a concatenation of diverse social movements arose unexpectedly in Latin America, culminating in massive anti-free market demonstrations. These events ushered in governments in Argentina, Bolivia, Ecuador, and Venezuela that advocated socialization and planning, challenging the consensus over neoliberal hegemony and the weakness of movements to oppose it. Eduardo Silva offers the first comprehensive comparative account of these extraordinary events, arguing that the shift was influenced by favorable political associational space, a reformist orientation to demands, economic crisis, and mechanisms that facilitated horizontal linkages among a wide variety of social movement organizations. His analysis applies Karl Polanyi's theory of the double movement of market society to these events, predicting the dawning of an era more supportive of government intervention in the economy and society.
Keywords: Latin America; double movement; market society; neoliberalism; political science / comparative politics; political science / world / general

Karl Polanyi's Great Transformation and Development Politics - Deutschmann, Moritz (Grin Verlag, 2009)
English, abstract: Attempts to understand the transformation processes in the developing world have often led to a closer examination of Europe′s and America′s own history, as many theories of development suggest a specific interpretation of these histories: Modernization theorists, for example, see Europe′s and America′s history mainly as a straightforward progression towards welfare and democracy, eclipsing the aspects that do not fit into this picture, like the World Wars or the American Civil War. Therefore, although Karl Polanyi′s "The Great Transformation" treats mainly historical events in Europe, it can at the same time be an important contribution to our understanding of the economic and social transformations in the developing world. In this essay, I will first try to make clear, what assumptions underlie Polanyi′s argument and what he means by the notion of "market society." I will proceed in three steps: first, I will explore the different roles that the economy, according to Polanyi, plays in capitalist and pre-capitalist societies; I will look then at the historical processes that led to the rise of a "market society." Finally, I will discuss the political reactions to these processes which can be characterized, in Polanyi′s view, by a "double movement." As Polanyi is one of the most important critics of economic liberalism, it is helpful to compare his account of the "Great Transformation" to a second, even more influential anti-liberal perspective, Marxism. Apart from some similarities, the fundamental difference seems to be that Polanyi does not give a positive account of modernization. This leads to the question, how Polanyi′s theori
Keywords: Great Transformation, The (Book); development; double movement; market society; modernization

Genealogies of Citizenship: Markets, Statelessness, and the Right to Have Rights - Somers, Margaret R. (Cambridge University Press, 2008)
REVIEW: Genealogies of Citizenship is a remarkable rethinking of human rights and social justice. As global governance is increasingly driven by market fundamentalism, growing numbers of citizens have become socially excluded and internally stateless. Against this movement to organize society exclusively by market principles, Margaret Somers argues that socially inclusive democratic rights must be counter-balanced by the powers of a social state, a robust public sphere and a relationally-sturdy civil society. Through epistemologies of history and naturalism, contested narratives of social capital, and Hurricane Katrina's racial apartheid, she warns that the growing authority of the market is distorting the non-contractualism of citizenship; rights, inclusion and moral worth are increasingly dependent on contractual market value. In this pathbreaking work, Somers advances an innovative view of rights as public goods rooted in an alliance of public power, political membership, and social practices of equal moral recognition - the right to have rights. "Building on Karl Polanyi, T. H. Marshall, and Hannah Arendt. Margaret Somers demonstrates that civil society rests on Ihe right to have rights. But this right has been swept away by three decades of market-dominated discourse and policies. Somers brilliantly shows how Hurricane Katrina's devastating impact on New Orleans was the culmination of this dynamic." -Fred Block
Keywords: ARENDT, Hannah; citizenship; civics and citizenship; civil rights; history / Europe / general; political science - history and theory; right to have rights

America transformed: globalization, inequality, and power - Hytrek, Gary J.; Zentgraf, Kristine M. (Oxford University Press, Incorporated, 2008)
Globalization--the interconnection of the world culturally, socially, politically, and economically--has generated intense theoretical and practical concerns. Is globalization inevitable? What are the effects of globalization on social structures and individual perceptions? What is the effect of globalization on societal level inequality? America Transformed: Globalization, Inequality, and Power examines these questions by analyzing the links among global processes and shifting patterns of stratification, inequality, and social mobility in the United States. While many texts separate discussions of macro- and micro-level processes when examining globalization, this book skillfully integrates general macro-level processes with specific reference to the micro-level effects of globalization in the U.S. Exploring the critical dimensions of inequality--class, gender, and immigration--America Transformed situates the U.S. experience within the broader global context, and fleshes out the mechanism through which global processes affect social stratification. By examining the social construction of globalization, the authors identify the key policy challenges of globalization, and some of the innovative community-based responses to social inequality.America Transformed provides powerful insights into the contested dialectical relationship between global and local forces: how globalization shapes stratification and inequality in the U.S., and how local communities attempt to mediate those changes.
Keywords: globalization; social classes; social science / sociology / general

The political economy reader: markets as institutions - Barma, Naazneen; Barma, Naazneen H.; Vogel, Steven Kent (Routledge, 2007)
This reader combines in a single volume the key writings of classical and contemporary thinkers on political economy. The articles provide both a theoretical approach to understanding capitalism and a survey of the varieties of capitalism around the world today, examining the interaction between politics and markets both in theory and practice. Drawing on history, economics, political science and sociology, it emphasizes the ways in which markets are embedded in and influenced by political and social institutions. Steven K. Vogel and Nazneen Haider Barma provide an informative overview of a number of the most significant controversies and contemporary debates in political economy through the selections of contending perspectives on a variety of issues, including: How can rich countries make their economies more competitive? How can poor countries achieve economic development? How can post-communist countries make a successful transition to markets? Will theinformation technology revolution render the national varieties of capitalism obsolete? Does globalization imply that the national varieties of capitalism will converge to one global capitalism? A Political Economy Reader will be an essential resource for students of political economy and economic sociology.
Keywords: business & economics; capitalism; economics; international economic relations; political economy; political science; sociology

The Transnational Politics of Corporate Governance Regulation - Overbeek, Henk; Apeldoorn, Bastiaan van; Nölke, Andreas (Routledge, 2007)
This ambitious volume explores the politics of recent changes in corporate governance regulation and the transnational forces driving the process. Corporate governance has in the 1990s become a catchphrase of the global business community. The Enron collapse and other recent corporate scandals, as well as growing worries in Europe about the rise of Anglo-Saxon finance, have made issues of corporate governance the subject of political controversies and of public debate. The contributors argue that the regulation of corporate governance is an inherently political affair. Given the context of the deepening globalization of the corporate world, it is also increasingly a transnational phenomenon. In terms of the content of regulation the book shows an increasing reliance on the application of market mechanisms and a tendency for corporations themselves to become commodities. The emerging new mode of regulation is characterized by increasing informalization and by forms of private regulation. These changes in content and mode are driven by transnational actors, first of all the owners of internationally mobile financial capital and their functionaries such as coordination service firms, as well as by key public international agencies such as the European Commission. The Transnational Politics of Corporate Governance Regulation will be of interest to students and researchers of international political economy, politics, economics and corporate governance.
Keywords: NGOs; NGOs (non-governmental organizations); business & economics; economic policy; international political economy; political science; public policy

Globalization and Contestation: The New Great Counter-Movement - Munck, Head of Civic Engagement Dublin City University and Visiting Professor of Development Studies University of Liverpool and St Mary's University Nova Scotia Ronaldo; Munck, Ronaldo (Routledge, 2006)
Globalization is undoubtedly the great overarching paradigm of our era. However, there is still little agreement on what globalization actually ‘is’ and some do not accept that it ‘is’ anything at all. This new book addresses the contestation of globalization by the anti- or counter-globalization movement. To contest means to challenge, to call into question, to doubt, to oppose and to litigate. This study shows how globalization is ‘contestable’ in many different ways and how the counter-movements we have seen emerging over the last decade also ‘bear witness’ on behalf of an alternative human future. Ronaldo Munck presents an overarching framework that allows us to understand how globalization and its contestation are inextricably bound up with one another. This volume insightfully explores a number of case studies, including: the battle of Seattle in 1999 the World Social Forum peasant internationalism environmental movements and reactionary movements including: the US Patriot's movement, Islamic fundamentalist movements and other nationalist movements. Globalization and Contestation will be of great interest to all students and scholars of international relations, politics and of globalization and global governance in particular.
Keywords: countermovement; globalization; political economy; political science

Beyond Globalization: Capitalism, Territoriality and the International Relations of Modernity - Lacher, Hannes (Routledge, 2006)
Hannes Lacher presents a new critical social theory of international relations that integrates sociology, history and political geography to understand the formation and development of modern international relations. Far from implying a return to state-centrist Realism, this essential new volume leads us towards a critical social theory of international relations that questions the prevailing conceptions of the modern international political economy as a collection of nationally bounded spaces more fundamentally than ever before. It also shows us that capitalist modernity itself was, from the beginning, characterized by the dualism of global economic integration and the fragmentation of political space, which actually stems from the divergent origins of capitalism and territorial sovereignty. This book will be of great interest to al students of historical sociology, political geography, international relations and political science.
Keywords: international political economy; international relations

Vulnerability and violence: the impact of globalisation - Kirby, Peadar (Pluto, 2006)
'Vulnerability' is now a key term in globalisation studies. It is used to describe how globalisation impacts on individual security, local communities and even global flows of trade, finance and investment. Yet there has been little attempt to interrogate the term and what it is trying to express about globalisation.Peadar Kirby examines what is really meant by 'vulnerability' and links it to new forms of violence that have resulted from decreased security and social cohesion. He argues that vulnerability and violence are characteristic features of a new world order dominated by neoliberal globalisation. Illustrating his argument with a wealth of examples taken from all over the world -- from the sudden collapse of the middle class in Argentina to increased levels of poverty internationally -- he offers a robust theoretical grounding that will be of use to anyone studying vulnerability and violence and their relation to contemporary globalisation.
Keywords: globalization; globalization - economic aspects; globalization - social aspects; international security; national security; political freedom & security; violence; violence in society

Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Polanyi Levitt, Kari; McRobbie, Kenneth (Black Rose Books, 2006)
Karl Polanyi’s belief that the greatest threat to freedom was a poorly administered economy led him to an economics that was more existential and human-centered. Part I of this book develops Polanyi’s thinking for its significance today through a selection of papers on re-reading his major work entitled The Great Transformation. Part II looks at the life and work of Ilona Duczynska (Polanyi’s wife), political activist, writer and translator and important influence over Karl and his work. Kenneth McRobbie, a poet and historian who teaches at the University of British Columbia, is the editor of Humanity, Society and Commitment. Kari Polanyi Levitt, emeritus professor at McGill University, is the editor of The Life and Work of Karl Polanyi.
Keywords: autobiography; biography; business & economics

The Global Resistance Reader - Amoore, Louise (Psychology Press, 2005)
The Global Resistance Reader provides the first comprehensive collection of work on the phenomenal rise of transnational social movements and resistance politics: from the visible struggles against the financial, economic and political authority of large international organizations such as the World Trade Organization, World Bank and International Monetary Fund, to the much less visible acts of resistance in everyday life. The conceptual debates, substantive themes and case studies have been selected to open up the idea of global resistance to interrogation and discussion by students and to provide a one-stop orientation for researchers, journalists, policymakers and activists.
Keywords: GILL, Stephen; political science / globalization; political science / reference

Citizenship unbound: The global politics of neo-liberalism and labor migration - Barker, Isabelle Virginie; Cornell, Drucilla (2005)
This dissertation considers the status of citizenship in an era of neo-liberal globalization. Citing increased labor migration and the retreat of domestic social policies throughout the world as intersecting processes, I argue that narratives of national citizenship lie at the heart of this intersection, transformed by rapidly changing geopolitical conditions. Despite challenges, national citizenship remains a relevant political category, though reformulated along the lines of neo-liberal principles of privatization, market rationality, and individual responsibility. the politics and rhetoric surrounding the 1996 federal reforms of immigration and social policy in the United States serve as one example of this process. I further support my claim with an extensive illustration of the linkages between the restructuring of U.S. health care policy for senior citizens with the increased migration of women from the global South to provide low-wage direct care services for the aging population in the United States. I then evaluate the work of Martha Nussbaum, Amartya Sen and Thomas Pogge, arguing that their respective efforts fail to offer effective interventions into the fate of democratic citizenship in an era defined by expanding inequalities and shrinking public spaces. I conclude by bringing together the works of Karl Polanyi, David Held, and Hannah Arendt with feminist scholarship to develop a feminist theory of democracy and political membership for the twenty-first century. (Copyright applies to all Abstracts.)
Keywords: ARENDT, Hannah; HELD, David; NUSSBAUM, Martha; POGGE, Thomas; SEN, Amartya; citizenship; feminist theory; globalization; labour migration; political science; women's studies

The Economy as a Polity: The Political Constitution of Contemporary Capitalism - Joerges, Christian; Stråth, Bo; Wagner, Peter (Psychology Press, 2005)
The debate about so-called economic globalization has reached a new phase. The hegemony of neo-liberal thinking has ended, in the face of both the increased and increasingly effective resistance to the social consequences of neo-liberal market-making - rising inequality and insecurity throughout the world - and the visibly dysfunctional effects of lack of regulation - currency and stock market crashes, among others. Thus, the story about 'the rise and fall of market society', which was first told in these terms by Karl Polanyi sixty years ago, is about to receive a new chapter. In this light, this volume offers a novel perspective on the interaction between states and markets. In contrast to much of current theoretical wisdom, we hold, with Polanyi, that markets cannot even be consistently thought of as self-regulating. Markets are always constituted by framework conditions that cannot be set by the markets themselves. The range and scope of market rules requires some agreement, or at least acceptance, for economic exchange to be working at all; in democratic societies, these rules are at least theoretically always subject to political debate and decision. To put the issue in theoretical terms: even the most pure version of economic liberalism always entails at the same time a political philosophy. This volume, thus, proposes to understand contemporary capitalism by regarding the economy as a polity, as an arrangement that is always constituted by some collective agreements about its mode of operation. Such theoretical position on its own, though, is insufficient to explain the workings of capitalism once and for all. Historical experiences with capitalism have led to transformations that require new angles of analysis. It is in the nature of the struggles over the embedding of markets that their outcomes are subject to historical contingency and cannot be completely known beforehand. Beyond a review of the theoretical tools at hand, therefore, the analysis of the contemporary constellation of capitalism, also requires an understanding of its recent transformations. This is the second task to which this volume is devoted - through analyses of the current state of regulation of labour and money and through investigations of the historical development and novel forms of the mode of embedding markets. While focusing on the renewal of the analysis of contemporary capitalism, the volume also points to fruitful directions of institutional or policy change and provides perspectives for a much-needed political renewal, with a particular focus on the European Union as a novel polity embedding the European economy.
Keywords: business & economics; economic policy; free enterprise; public policy

Surviving Capitalism: How We Learned to Live with the Market and Remained Almost Human - Ringmar, Erik (Anthem Press, 2005)
Human life cannot be reduced to market transactions and human beings cannot only be treated as economic actors. When the power of the market increases, human beings will always try to protect themselves. Given the differences that exist in social and cultural traditions, these protective responses are likely to differ from one society to the other. This is why, even in a global market, diversity is always likely to persist. This book investigates the question of economic globalization - whether it is likely to lead to full convergence between political models and ways of life, or whether, even in a completely globalized world economy, there is likely to be scope for alternative solutions. But in a fully globalized world, how will we survive capitalism?
Keywords: economic globalization; globalization

International Relations and the Problem of Difference - Inayatullah, Naeem; Blaney, David L. (Routledge, 2004)
International Relations and the Problem of Difference has developed out of the sense that IR as a discipline does not assess the quality of cultural interactions that shape, and are shaped by, the changing structures and processes of the international system. In this work, the authors re-imagine IR as a uniquely placed site for the study of differences as organized explicitly around the exploration of the relation of wholes and parts and sameness and difference-and always the one in relation to the other. KM: Chapter 5 "Toward an Ethnological IPE" deals extensively with Polanyi's ideas
Keywords: economic anthropology; ethnological IPE; international political economy; international relations; political economy

Environmental Values in a Globalizing World: Nature, Justice and Governance - Lowe, Ian; Paavola, Jouni (Routledge, 2004)
This multidisciplinary volume presents a refreshing new approach to environmental values in the global age. it investigates the challenges that globalization poses to traditional environmental values in general as well as in politics and international governance.Divided into five parts, the book investigates how environmental values could be reconceived in a globalizing world.Part I explores contemporary environmental values and their implications for a globalizing world.Part II examines the development of Western and Eastern environmental valuesPart III discusses contemporary environmental politicsPart IV examines how values inform environmental governance and how governance solutions influence which values are realisedPart V concludes the volume with two different views of the prospects of environmental values in a globalising world. This study will be of great interest to students and researchers studying the environment in philosophy, political science, international relations, international environment law, environmental studies and development studies. KM - Contains chapter: "Global Liberalism, Environmentalism, and the Changing Boundaries of the Political : Karl Polanyi's Insights" by John M. Meyer
Keywords: MEYER, John M.; environmental policy; globalization; public policy

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (Cambridge University Press, 2004)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
Keywords: Europe; history; international relations; political science - history and theory

The Meaning of Freedom in a Complex Society: The Development of Karl Polanyi's Thought on Economics, Modernity, and Human Liberty - Katsh, Gabriel (Harvard University, 2004)
Keywords: freedom in a complex society

Desolation and Enlightenment: Political Knowledge After Total War, Totalitarianism, and the Holocaust - Katznelson, Ira (Columbia University Press, 2004)
During and especially after the Second World War, a group of leading scholars who had been perilously close to the war's devastation joined others fortunate enough to have been protected by distance in an effort to redefine and reinvigorate Western liberal ideals for a radically new age. Treating evil as an analytical category, they sought to discover the sources of twentieth-century horror and the potentialities of the modern state in the wake of western desolation. In the process, they devised strikingly new ways to understand politics, sociology and history that reverberate still. In this major intellectual history, Ira Katznelson examines the works of Hannah Arendt, Robert Dahl, Richard Hofstadter, Harold Lasswell, Charles Lindblom, Karl Polanyi, and David Truman, detailing their engagement with the larger project of reclaiming the West's moral bearing. In light of their epoch's calamities these intellectuals insisted that the tradition of Enlightenment thought required a new realism, a good deal of renovation, and much recommitment. This array of historians, political philosophers, and social scientists understood that a simple reassertion of liberal modernism had been made radically insufficient by the enormities and moral catastrophes of war, totalitarianism, and holocaust. Confronting their period's dashed hopes for reason and knowledge, they asked not just whether the Enlightenment should define modernity, but which Enlightenment we should wish to have. Decades later, in the midst of a new type of war and reanimated discussions of the concept of evil, we share no small stake in assessing their successes and limitations.
Keywords: ARENDT, Hannah; World War II; fascism; military history; political history; political philosophy; political theory; totalitarianism

Globalization: People, Perspectives, and Progress - Mott, William H. (Greenwood Publishing Group, 2004)
This study expands the narrow economic-commercial focus of the topical media and places globalization in a multidisciplinary context as a continuing process and a permanent condition that transforms human living and society. Early chapters review the development of globalization as creating and diffusing knowledge, expanding people's perspectives on living, and continuing progress. These chapters introduce globalization as an iterative, human, and deliberate process of creating new knowledge and using it to reinterpret the world, time, and man's place in both. The later chapters present the major analytical perspectives of globalization--political, cultural, and economic--and a comparison of the primary carriers of globalism and barriers to globalization.Drawing on classical and modern analysis, as well as narrow, topical journalism, the work focuses each perspective on people through the human processes of creating knowledge and living together. The work expands the economic perspective beyond the fashionable focus on trade and investment into the triggering and shadowing relationships between economic growth, political conflict, and social stress. The political perspective expands international politics and law to global governance, triadic dispute resolution, and global civil society. The cultural and antiglobal perspectives reflect the success of economic globalization in bringing people directly into the narrowly rational processes of international politics and economics. The final analytical chapter collects and compares observations and develops conclusions about globalization across the several perspectives. Speculation about alterative futures for globalizing humanity can constitute a coherent standard, ideal, or direction for policymaking, or an agenda for continuing research and debate.
Keywords: comparative politics; political science; social science

Democracy and the Global System: A Contribution to the Critique of Liberal Internationalism - Biancardi, F. (Palgrave Macmillan UK, 2003)
Jacket abstract: "Democracy and the Global System analyses the relationship between liberal democracy and the global system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts, including Barrington Moore Jr., Karl Polanyi, Joseph Schumpeter, Samuel Huntington and David Held. While sympathetic to the aim of spreading liberal democracy globally, he demonstrates the many tensions and contradictions involved in achieving this outcome." Google books: What are the prospects of the liberal democratic form of state spreading throughout the world? Democracy and the Global System analyses the relationship between liberal democracy and the international system while developing a critique of liberal internationalism. Fabian Biancardi examines some of the key questions of modern politics and the major ideas of a number of significant authors and texts. While sympathetic to the aim of spreading liberal democracy, he demonstrates the many tensions and contradictions involved in achieving this outcome.
Keywords: democracy; international relations; political ideologies; political science

Great Transformations: Economic Ideas and Institutional Change in the Twentieth Century - Blyth, Mark (Cambridge University Press, 2002)
Mark Blyth argues that economic ideas are powerful political tools as used by domestic groups in order to effect change since whoever defines what the economy is, what is wrong with it, and what would improve it, has a profound political resource in their possession. Blyth analyzes the 1930s and 1970s, two periods of deep-seated institutional change that characterized the twentieth century. Viewing both periods of change as part of the same dynamic, Blyth argues that the 1930s labor reacted against the exigencies of the market and demanded state action to mitigate the market's effects by "embedding liberalism" and the 1970s, those who benefited least from such "embedding" institutions, namely business, reacted against these constraints and sought to overturn that institutional order. In Great Transformations, Blyth demonstrates the critical role economic ideas played in making institutional change possible and he rethinks the relationship between uncertainty, ideas, and interests on how, and under what conditions, institutional change takes place. Mark Blyth is an assistant professor of political science at the Johns Hopkins University specializing in comparative political economy. He has taught at Columbia University, and at the University of Birmingham, UK. Blyth is a member of the editorial board of the Review of International Political Economy.
Keywords: economic policy; political economy; political science; public policy

Constructing a European Market: Standards, Regulation, and Governance - Egan, Michelle P. (Oxford University Press, 2001)
'An excellent contribution to our understanding of the political construction of markets... This is a well-written book, enjoyable to read as well as being very informative. I view this volume as a 'must read' for all scholars and graduate students in the areas of government and business, the politics of market economies and comparative politics in general. Michelle Egan's description and explanation of market construction and its impact on business standards, regulation and governance will be valuable to all of us for many, many years to come.' -Henry Jacek, McMaster University; Polibus: Newsletter of the IPSA Research CommitteeThis book provides a detailed analysis of the policies and institutions used by the EU to create a single market. Through a historical overview, sectoral case studies, and an assessment of recent policy initiatives, the author provides a comprehensive account of the evolution of European economic integration.
Keywords: European Court of Justice; European Union; United States; business & economics; economic policy; harmonization; market integration; mutual recognition; public policy; regulation; single market; standards; trade barriers

The Rise of the Capital-State and Neo-Nationalism: A New Polanyian Moment - Svitych, Oleksandr (Brill, 2022)
Keywords: critical social sciences; global studies; neo-nationalism; populism; social sciences; sociology & anthropology

Constituting the Political Economy of the Kurds: Social Embeddedness, Hegemony, and Identity - Tekdemir, Omer (Routledge, 2021)
This book examines the development of Kurdish political economy and the emergence of collective Kurdish identity within a historical context through three main periods: the late-Ottoman Empire, the initial Republican Turkey era, and then the post-1990s period. It relates historical developments to the dynamics of Kurdish society, including the anthropological realities of the nineteenth century through the moral economy frame, the evolving nature of nationalism in the early twentieth century and the more recent construction of a modern political Kurdishness by means of radical democracy, and an agonistic pluralism shaped by left-wing populism.
Keywords: Kurdistan; Political Science / World / Middle Eastern; embeddedness; ethnic studies; middle eastern studies; regional studies

Karl Polanyi and Twenty-first-century Capitalism - Desai, Radhika; Levitt, Kari Polanyi (Manchester University Press, 2020)
As far right movements, social disintegration and international conflict emerge from the decay of the neoliberal order, Karl Polanyi's warnings against the unbridled domination of markets, is ever more relevant. The essays in Karl Polanyi for the 21st Century extend the boundaries of our understanding of Polanyi's life and work. They will interest Polanyi scholars and all interested in socialism and our future after neoliberalism. One asks whether, following Keynes and Hayek, Polanyi's ideas will shape the twenty-first century. Some clarify, for the meaning of money as a fictitious commodity. Others resolve difficulties in understanding the building blocks of Polanyi's thought: fictitious commodities, the double movement, the United States' exceptional development, the reality of society, and socialism as freedom in a complex society. And yes others explore how Polanyi sheds light on income inequality, world systems theory, comparative political economy.
Keywords: capitalism; double movement; neoliberalism; reality of society; socialism